2020
DOI: 10.3390/ani10010121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytase Derived from the E. coli AppA Gene on Weaned Piglet Performance, Apparent Total Tract Digestibility and Bone Mineralization

Abstract: The objective of this study was to assess the effect of novel appAT1 and appAT2 phytase inclusion at 250 phytase units (FTU)/kg on weaned piglet performance, the apparent total tract digestibility of P and Ca, and bone mineralization. Piglets (48 males) were randomly divided into four treatment groups: a positive control (PC), with recommended levels of phosphorus (P) and calcium (Ca), a negative control (NC) deficient in P and Ca, and two experimental groups with NC diets supplemented with phytase derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In another study, Varley et al [38] showed no significant differences in FI, ADG, or FCR in weaned piglets with a body weight of approximately 33 kg, fed a diet with an adequate amount of P supplemented with phytase at a dose of 500, 1000, or 1500 FTU/kg, during the weaner and grower-finisher periods [38]. In contrast, in the recent study Wiśniewska et al [39] showed that the phytase supplemented to the calcium-and phosphorus-deficient diet at a dose of 250 FTU/kg for a period of 42 days significantly improved ADG and FCR, as well as ADC for Ca and P compared to the control calcium-and phosphorus-deficient diet [39]. ADC for phosphorus availability in a study by Dersjant-Lia et al was significantly higher, but only compared with the phosphorus-deficient diet, and increasing the phytase dose had no effect [34].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In another study, Varley et al [38] showed no significant differences in FI, ADG, or FCR in weaned piglets with a body weight of approximately 33 kg, fed a diet with an adequate amount of P supplemented with phytase at a dose of 500, 1000, or 1500 FTU/kg, during the weaner and grower-finisher periods [38]. In contrast, in the recent study Wiśniewska et al [39] showed that the phytase supplemented to the calcium-and phosphorus-deficient diet at a dose of 250 FTU/kg for a period of 42 days significantly improved ADG and FCR, as well as ADC for Ca and P compared to the control calcium-and phosphorus-deficient diet [39]. ADC for phosphorus availability in a study by Dersjant-Lia et al was significantly higher, but only compared with the phosphorus-deficient diet, and increasing the phytase dose had no effect [34].…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, the phytase added at the dose of 500 FTU/kg to a calcium-and phosphorus-deficient diet increased BMD of metacarpal bone in pigs at slaughter [43]. There are, however, other studies that observed no effects of phytase supplementation on bone mineral content (BMC) or bone ash of metacarpal bones, but these studies made use of calcium-and phosphorus-deficient diets supplemented with phytase at a dose of 500 or a dose of 250 FTU/kg [39,44]. It can be due to fact that in different bones, changes in ash content, BMC, and BMD are observed due to their different phosphorus supply [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the strains of this species, Z129 possessed unique genes including app A, nrf A, and wec E. The expression of app A significantly improves phytase activity ( Chiera et al, 2004 ), which can increase the efficiency of phytate phosphorus ( Beaulieu et al, 2007 ). The addition of phytases improves the final body weight and feed conversion ratio of weaned piglets fed with a diet lacking in calcium and phosphorus ( Wiśniewska et al, 2020 ). Gene nrf A can be involved in catalysis of the second step of dissimilatory nitrate reduction to ammonium to reduce nitrogen loss and protects the environment ( Tiedje, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phytase enzyme that is the subject of this paper, Phytase TSP concentrate, to be marketed under the trade name OptiPhos® PLUS, is a novel thermostable 6-phytase developed for use as an ingredient in animal feed. Studies in weaned piglets and broiler chickens have demonstrated the high in vivo bioefficacy of the phytase [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%